ERS International Congress, Madrid, 2019: highlights from the Airway Diseases, Asthma and COPD Assembly. Issue 1 (17th February 2020) - Lahousse, Lies; Bahmer, Thomas; Cuevas-Ocaña, Sara; Flajolet, Pauline; Mathioudakis, Alexander G.; McDonnell, Melissa; Uller, Lena; Schleich, Florence; Dortas Junior, Sergio; Idzko, Marco; Singh, Dave; Ricciardolo, Fabio L.M.; et al.
The European Respiratory Society (ERS) International Congress 2019 in Madrid, Spain, was a platform for scientific discussion of the highest quality scientific research, cutting-edge techniques and innovative new therapies within the respiratory field. This article discusses some of the high-quality research studies presented at that Congress, with a focus on airway diseases, including asthma, COPD, small airways, bronchiectasis and cough, presented through the Airway Diseases, Asthma and COPD Assembly (Assembly 5) of the ERS. The authors establish the key take-home messages of these studies, compare their findings and place them into context of current understanding. This article discusses some of the high-quality research studies presented at #ERSCongress in Madrid, with a particular focus on airway diseases, presented through the Airway Diseases, Asthma and COPD Assembly (Assembly 5) http://bit.ly/2RpDVvv